Synthesis and characterization of novel value added biodegradable poly(aleuritic acid) from renewable resources(shellac) and invertible amphiphilic behaviors in various solvents - Pandey, Asutosh K.; Nande, Smita S.; Selukar, Balaji S.; Garnaik, Baijayantimala (E-Polymer, 2010)
A novel biodegradable polymer poly(aleuritic acid) (PAA) ( M̄w 120,000) was prepared from aleuritic acid, which was obtained from renewable resources (Lac) by using tin catalyst. Aleuritic acid (AL) was protected at 9, 10 position by dimethoxy propane. The protected AL (Pro.AL) was further polymerized to obtain linear protected polyaleuritic acid (PAL) by dehydropolycondensation. Effects of various kinetic and thermodynamic parameters were studied. After polymerization, the deprotection of PAL was carried out. The synthesized PAL and PAA were characterized by using various techniques such as FT-IR, LC-MS, SEC, NMR (1H and 13C), 13C CP/MAS (Cross Polarization / Magic Angle Spinning) of solid PAA, DSC, SEM and TEM etc. The micelle and inverted micelle -structure in polar and nonpolar solvents are highlighted

Study of grafting of polylactic acid and its copolymer with 12-hydroxy stearic acid on the surface of MWCNT by 13CCP/MAS and AFM - Pandey, Asutosh K.; Garnaik, Baijayantimala (International Journal of Research in Pharmacy and Chemistry, 2013)
The purpose of this study to study the structure property relationship of grafted material on MWCNT, the determination of NMR nuclei spin-lattice (T1) and spin-spin (T2) relaxation times suggest that the broaden signals are associated with diamagnetic species namely the nanotube attached polymer moieties. the AFM image of PLA oligomer grafted MWCNTs and topography patterns comprised of height from 0-250 nm and the side lengths ranging from 0.0 to 7.7 µm. Surface patches are formed randomly distributed employing that the presence of side chain hanged at 12-postion in the copolymer grafted on MWCNTs.